(untitled) (Journal of the College of Basic Education, 2022)
This research aims to know the effect of landforms (terrain) on the process of liberating the Jurf Al-Nasr area (formerly Al-Sakhr) and to know the negatives that faced that process in general and in the operations sector in particular, as well as to solve the problems that resulted from those operations and their risks to the security forces, and ways to address them And what are the best ways to reduce and benefit from it, and use these methods to liberate other regions?